Incidence and differential characteristics of culture‐negative fever following pancreas transplantation with anti‐thymocyte globulin induction. Issue 5 (23rd September 2016) - Shin, S.; Kim, Y.H.; Kim, S.‐H.; Lee, S.‐O.; Kwon, H.W.; Choi, J.Y.; Han, D.J.
Abstract: Background: Limited data are available on the incidence and characteristics of culture‐negative fever following pancreas transplantation (PTx) with anti‐thymocyte globulin (ATG) induction. Our study aims to better define the features of culture‐negative fever, so it can be delineated from infectious fever, hopefully helping clinicians to guide antibiotic therapy in this high‐risk patient population. Methods: We performed a retrospective cohort study of postoperative fever among 198 consecutive patients undergoing PTx at our center between August 1, 2004 and December 31, 2014. Fever was classified as culture‐negative if there was neither a positive culture nor a documented clinical diagnosis of infection. Results: Fever was identified in 113 patients; 66 were deemed to be infectious, 39 were culture‐negative, and 8 were indeterminate. High body mass index of recipient (odds ratio 1.87, 95% confidence interval: 1.15–3.03, P = 0.011) was a significant factor associated with culture‐negative fever in multivariate analysis. No patients with culture‐negative fever were diagnosed with infiltrates or effusion on chest radiography. In addition, an increase in white blood cell count, C‐reactive protein, and serum amylase was less prominent in culture‐negative fever. Culture‐negative fever developed most frequently at postoperative 7 or 14 days, showing a biphasic curve. Conclusion: Culture‐negative fever develops in a substantial proportion of patients early after PTx. The awareness of the possibility and clinical features of post‐transplant culture‐negative fever might help clinicians to guide antibiotic therapy in this high‐risk patient population, especially following ATG induction and early steroid withdrawal.